The congruence of SDG communication in formal and informal channels performed by self-titled sustainable companies - Oliveira, Paulo Roberto Vieira de; Alberton, Anete; Kreich, Mateus (Revista de Administração da UFSM, 2021)
Objective – Identify whether companies with substantial aspects related to sustainability and corporate social Responsibility (CSR) with high market values are consistent with what is presented in sustainability reports with posts on social media. Methodology – The virtual communities investigated were based on Interbrand rankings, the most valuable brands, and the Dow Jones Sustainability Index. Twitter was the social network chosen and elements of the netnography approach were used together with content and document analysis, in addition to network analysis exploration, with support of UCINET. Results – The hashtags most adopted by companies were #ClimateChange, #CleanEnergy, #climate, #climateaction, which are directly related to the Sustainable Development Goals – SDGs. The results showed that companies had communicated their actions related to the SDGs through the social network Twitter. However, some of them still do not adequately explore this tool. Limitations/Research implications - As a limitation of the research, it was not easy to locate some communities in which companies publish their hashtags referring to the SDGs. In addition, some companies do not present the actions related to the SDGs in their sustainability reports. Originality - The use of network analysis and content and document analysis proved to be effective in obtaining the results. This element is understood as an essential methodological contribution due to its originality in the communication of sustainable actions.